I want to prove the following equation but don't know how to get rid of these factorials.

Printable View

- Jan 14th 2009, 09:29 AMtotalnewbieGetting rid of factorials
I want to prove the following equation but don't know how to get rid of these factorials.

- Jan 14th 2009, 09:45 AMo_O
Are you sure you have to prove it? Try picking a few random numbers: $\displaystyle

\begin{cases} n = 3 & m = 2 \\ p = 1 & q = 2 \end{cases}$

$\displaystyle \frac{n!}{(m-1)!(n-m+1)!}p^{m-1}q^{n-m+1} = \frac{3!}{(2-1)! (3-2+1)!} (1)^{2-1} (2)^{3-2+1} = 12$

$\displaystyle mq = (2)(2) = 4$ - Jan 14th 2009, 10:04 AMtotalnewbie
That equation is associated with probability, so p=1-q.